Human rights and their protection in the inter-American and international arenas: The Lhaka Honhat case, Salta, Argentina - Soriano, Gonzalo Victor Humberto (2023)
The purpose of this article is, on the one hand, to reflect and problematize the notion of human rights in Latin America. On the other hand, to describe and analyze the instruments and mechanisms of international and inter-American protection of human rights that promote tools for their respect and guarantees for all people. Finally, an attempt is made to analyze the Lhaka Honhat case, taking into account the institutional frameworks that the Inter-American System for the Protection of Human Rights employs in the face of the alleged violation of the right to property to the detriment of the indigenous communities of the town of Rivadavia, Province of Salta, Argentina. The interest in addressing these objectives takes up the idea of ​​thinking about the protection of human rights as normative responses to problems and needs that occur in society. In this way, theoretical tools are used to discuss the conceptions that revolve around how human rights are currently understood and, in what way, certain instruments, mechanisms and systems at the international and inter-American levels promote their protection regarding indigenous peoples. Consequently, it is assumed that human rights make up a field of social, historical and cultural struggles for dignity, understanding them as equal access to goods necessary for life, the results of which must be guaranteed through legal, political and economic norms.